Afterslip and Triggered Slip Following the 6 Feb 2023 Kahramanmaraş Earthquake Sequence, East Anatolian Fault, Türkiye - Bilham, Roger; Ayruk, Efe Turan; Turğut, Muhammed; İrgüren, Recep; Köküm, Mehmet; Elhisso, Abdulrahman; Doğan, Uğur (Springer Nature, 2025)
We report triggered slip and afterslip following the Mw7.8 and Mw7.6 Kahramanmaraş, Türkiye earthquakes of 6 Feb 2023, as recorded by 13 carbon-rod extensometers installed across surface faults. These extensometers measure 6–54 m long and were installed at 30° to the fault with a resolution of 2 µm and range of 1.5 m. Three creepmeters were operating at the time of these earthquakes: two on the North Anatolian fault near Ismetpasa and a third on the East Anatolian fault near Sivrice. The earthquakes induced 5 mm of triggered slip at Ismetpasa, but only 1 mm of slip on the East Anatolian Fault at Sivrice. Both of these triggered slip events corresponded in amplitude to the release a local creep slip-deficit that had developed prior to the earthquakes. Seven afterslip meters installed along the central segments of the primary ruptures recorded negligible afterslip (<3 mm in 6 months) revealing that the fault in these locations was now locked. The remaining three instruments, at the northwestern and southeastern extremities of the mainshock ruptures revealed significant afterslip. At Goksun near the northwestern end of the Mw 7.6 rupture we recorded surface slip preceding local aftershocks, including a unique record of accelerating slip preceding a local Mw4.7 aftershock. A second region of continued slip occurs at the eastern end of the Mw 7.8 rupture known as the Puturge gap, a segment of the fault that also arrested coseismic slip in the Elazığ-Sivrice 2020 Mw 6.8 earthquake. The initial array of five extensometers here was supplemented by a further two. They reveal that?>?3.8 mm/yr of slip continues at depth. In September, three creepmeters here, over a distance of 45 km, recorded what appears to be an eastward propagating creep event in the subsurface. To investigate the evolution of subsurface slip further in the Puturge gap the five creepmeters have been supplemented with a 3-component 1-km-scale cGPS array recording at 5 Hz. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
3rd International conference on Mediterranean Geosciences Union, MedGU 2023 -- 26 November 2023 through 30 November 2023 -- Istanbul -- 342459
Keywords: Accelerating slip; Afterslip; Fault creep; Kahramanmaras earthquakes; Triggered slip